Anticancer Potency and Multidrug‐Resistant Studies of Self‐Assembled Arene–Ruthenium Metallarectangles. Issue 35 (12th July 2013) - Dubey, Abhishek; Min, Jin Wook; Koo, Hyun Jung; Kim, Hyunuk; Cook, Timothy R.; Kang, Se Chan; Stang, Peter J.; Chi, Ki‐Whan
Abstract A suite of three tetraruthenium metallacycles have been obtained from [2+2] self‐assemblies between N, N′‐Di‐(4‐pyridyl)‐1, 4, 5, 8‐naphthalenetetracarbo–xydiimide (4) and one of the three dinuclear arene ruthenium clips, (η6‐p‐iPrC6H4Me)2Ru2(OO∩OO)][OTf]2 (OO∩OO=oxalate 1, 2, 5‐dioxydo‐1, 4‐benzoquinonato (dobq) 2, 5, 8‐dihydroxy‐1, 4‐naphthaquinonato (donq) 3; OTf=triflate). All complexes were isolated in good yield (>85 %) as triflate salts and were fully characterized by using 1H NMR and UV/Vis spectroscopies, and high‐resolution electrospray mass spectrometry. A single crystal of the metallarectangle 5 was suitable for X‐ray diffraction structural characterization. The biological activities of the metallacycles were determined by using 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide (MTT) assays, establishing their in vitro anticancer properties. Our results show that for the AGC (gastric cancer) cell lines, the cytotoxicity of (donq)‐containing SCC 7 exceeds that of cisplatin, which was used as a control. For HCT15 (colon cancer) cell lines, the cytotoxicity is comparable to both cisplatin and doxorubicin. An in vivo hollow fiber model was used to show growth‐inhibitory activity against HCT15 and image‐based cytometry experiments indicated that 7 induced apoptosis as the mode of cell death. Complex 7 also showed significant antitumor activity for multidrug‐resistant HCT15/CLO2 cell lines, for which doxorubicin was ineffective.